Complete mitochondrial genome of Tringa erythropus (Charadriiformes: Scolopacidae) - Cheng, Yuanyuan (Mitochondrial DNA B Resour, 2016)
The spotted redshank Tringa erythropus is a shorebird in the large bird family Scolopacidae. In this study, we sequenced and characterized its complete mitochondrial genome. The mitogenome is a circular DNA molecule of 16,683 bp in length, containing 13 protein-coding genes, 22 tRNA, 2 rRNA genes, and an AT-rich region. Its gene arrangement pattern is identical with typical bird species. Based on our data combined with the mitgenome DNA sequences of 12 Scolopacidae birds from GenBank, phylogenetic analysis indicated that T. erythropus, Arenaria interpres, and Eurynorhynchus pygmeus formed a group.